Mathematical model of photoacoustic microscopy with piezoelectric detection - Vertsanova, E.V.; Yakimenko, Yu.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Mathematical model is formulated for piezoelectric detection of the photoacoustics effect in optically semitransparent and thermally thick object with subsurface non-homogeneity in the case of free holding a piezodetector in a photoacoustic cell of the respective microscope. The model enables to estimate the influence of subsurface defects on the photoacoustical signal and to take into account the contribution of this factor into output signal of investigated objects.